PENGARUH PENGGUNAAN BIG DATA DALAM PENGEMBANGAN DATA GOVERNANCE MENJAMIN KUALITAS DATA DI PERUSAHAAN TERHADAP KINERJA PERUSAHAAN - Ramanda putri; Muhammad Irwan Padli Nasution (JURNAL ILMIAH NUSANTARA, 2024)
The use of big data to develop data governance ensures that the quality of data in a company has a positive impact on company performance. Big data analytics technologies can help improve audit quality, manage large amounts of diverse data, and facilitate algorithmic decision making. Big data increases the efficiency and effectiveness of audits and allows data collection to reveal patterns and relationships that are not visible at first glance. In addition, the use of big data can help reduce the burden on infrastructure by identifying problem areas, developing the tourism sector, and improving the quality of emergency response.